A Practical Guide to Hospital Ministry - Koenig, Harold G, author.
1 online resource (336 pages)
Keywords: Examine a meaningful, integrated, systemic, and pragmatic view of hospital ministry!A Practical Guide to Hospital Ministry: Healing Ways is a comprehensive resource that examines the roles and responsibilities of hospital chaplains. It will help you make a shift toward a knowledge- and skill-based ministry that both incorporates and goes beyond current training approaches. In the words of author McCall, “In today’s healthcare and specialized ministry services, education and training must be progressive and thorough. It must include experiences that increase one’s expertise in working with individuals, groups, families, consumers, and systems. These services must be integrated into the total structure and resources of hospitals at all levels of mission, philosophy, and program. Furthermore . . hospital ministry must strive to be a resource to the wider community and the church.” A Practical Guide to Hospital Ministry is a vital resource for those who want to integrate hospital ministry into organizations whose support and understanding of the discipline are weak or do not exist at all.A Practical Guide to Hospital Ministry provides numerous resources that can be of immediate use to anyone engaged in hospital ministry, including: job descriptions descriptions of various types of hospital ministries scope-of-practice statements sample pastoral care brochures and request forms orientation checklists sample religious preference codes a list of typical counseling problems therapeutic referral and progress formsFor administrators, educators, and those seeking to provide spiritual and pastoral resources to hospitalized individuals and their families, A Practical Guide to Hospital Ministry will prove to be an invaluable reference work.